Association of placenta‐derived extracellular vesicles with pre‐eclampsia and associated hypercoagulability: a clinical observational study. (3rd November 2020) - Chen, Y; Huang, P; Han, C; Li, J; Liu, L; Zhao, Z; Gao, Y; Qin, Y; Xu, Q; Yan, Y; Wang, Y; Ren, J; et al.
Abstract : Objective: Pre‐eclampsia (PE) is a pregnancy‐associated condition initiated by placental factors. We have demonstrated that placental extracellular vesicles (pcEVs) cause hypertension and proteinuria in pregnant and non‐pregnant mice. Study design: An observational study with both case‐control and longitudinal designs. Setting: A single centre at the Department of Obstetrics and Gynaecology, Tianjin Medical University. Population: We collected blood samples and clinical information from 54 PE patients, 33 normally pregnant women at 30–36 gestational weeks and on postpartum days 1 and 4 for the cross‐sectional study, and at 22–31, 32–35 and 36–40 weeks for the longitudinal study. Non‐pregnant women were also recruited. Methods: Blood samples were analysed using flow cytometry, coagulation tests and ELISA. Main outcome measures: The primary outcome was plasma pcEV and other extracellular vesicles (EVs), and their expressions of anionic phospholipids and von Willebrand factor (VWF). Secondary variables included coagulation, ADAMTS‐13 and the anionic phospholipid‐binding proteins. Results: Plasma pcEVs progressively increased from pregnant women during non‐menstrual period (NW) to PE patients (interquartile range [IQR] for NW: 206/microlitre [116–255], normal pregnancy [NP]: 1108/microlitre [789–1969] and PE: 8487/microlitre [4991–16 752]) and predicted PE. EVs from endothelial cells, platelets and erythrocytes accounted for <10% of pcEVs. VWF became hyper‐adhesive in PE patients and contributed to the pregnancy‐associated hypercoagulability. Conclusion: Placental, platelet‐ and endothelial cell‐derived EVs were significantly elevated in PE patients, but only pcEVs predicted PE. These EVs played a causal role in the pregnancy‐induced hypercoagulability. Tweetable abstract: Placenta‐derived extracellular vesicles predict pre‐eclampsia and the associated hypercoagulability. Tweetable abstract: Placenta‐derived extracellular vesicles predict pre‐eclampsia and the associated hypercoagulability.